(untitled) (Publicaciones en Ciencias y Tecnología, 2012)
Disabled people need to rely on the use of technology to perform daily activities and work effectively and the couple of people without disabilities. In this sense, the objective of this experiment was to develop an educational proposal for the training of people with visual impairments in the use of office automation tools. The development of the program came from the request of the Palavecino Integration Team and based on documentary research monograph. Program design considered the conditions of people with visual impairments, the conditions must be the classroom, take their special educational needs and is based on the use of advanced technological tools to enable them to access the curriculum. The PCTecnoVisual was divided into 5 modules: Basic use of computers, Word, Excel, Power Point, Internet browsers and search engines, and has an estimated duration of 81 hours. Facilitators received 21 hours of training and Jaws 9.0 was used as the reader and Audio Testi 3.0 to translate the manuals to audio format.